Pituitary surgery as alternative to dopamine agonists treatment for microprolactinomas: a cohort study. Issue 6 (21st October 2021) - Baussart, Bertrand; Villa, Chiara; Jouinot, Anne; Raffin-Sanson, Marie-Laure; Foubert, Luc; Cazabat, Laure; Bernier, Michèle; Bonnet, Fideline; Dohan, Anthony; Bertherat, Jerome; Assié, Guillaume; Gaillard, Stephan
Abstract : Objective: Microprolactinomas are currently treated with dopamine agonists. Outcome information on microprolactinoma patients treated by surgery is limited. This study reports the first large series of consecutive non-invasive microprolactinoma patients treated by pituitary surgery and evaluates the efficiency and safety of this treatment. Design: Follow-up of a cohort of consecutive patients treated by surgery. Methods: Between January 2008 and October 2020, 114 adult patients with pure microprolactinomas were operated on in a single tertiary expert neurosurgical department, using an endoscopic endonasal transsphenoidal approach. Eligible patients presented with a microprolactinoma with no obvious cavernous invasion on MRI. Prolactin was assayed before and after surgery. Disease-free survival was modeled using Kaplan–Meier representation. A cox regression model was used to predict remission. Results: Median follow-up was 18.2 months (range: 2.8–155). In this cohort, 14/114 (12%) patients were not cured by surgery, including ten early surgical failures and four late relapses occurring 37.4 months (33–41.8) after surgery. From Kaplan–Meier estimates, 1-year and 5-year disease free survival was 90.9% (95% CI: 85.6–96.4%) and 81% (95% CI: 71.2–92.1%) respectively. The preoperative prolactinemia was the only significant preoperative predictive factor for remission ( P < 0.05). No severe complication was reported, with no anterior pituitary deficiency after surgery, one diabetes insipidus, and one postoperative cerebrospinal fluid leakage properly treated by muscle plasty. Conclusions: In well-selected microprolactinoma patients, pituitary surgery performed by an expert neurosurgical team is a valid first-line alternative treatment to dopamine agonists.